Digital Organizational Citizenship Behavior to Auditors' Satisfaction and Performance - Putra, Rizaldi; Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Veronica, Kristy (First Ciera Publisher, 2024)
The rapid digital transformation in the workplace has redefined Organizational Citizenship Behavior (OCB), particularly within professions such as auditing. This study explores Digital OCB, voluntary behaviors by auditors that enhance organizational functioning in digital contexts. Through a phenomenological approach, the study examines how digital OCB influences auditors' performance and job satisfaction. Findings indicate that digital OCB, including sharing digital resources, providing support via online tools, and maintaining a positive virtual presence, positively impacts job performance and satisfaction. However, challenges such as work-life boundary blurring and potential digital overload were noted. The study highlights that digital OCB is consistent with Social Exchange Theory, Role Theory, the Job Demands-Resources Model, Social Learning Theory, Organizational Support Theory, and the Technology Acceptance Model. Recommendations include fostering a supportive digital culture, training in digital communication, and implementing policies for work-life balance. Future research should investigate the long-term effects of digital OCB on career development and organizational performance.